2022
DOI: 10.1108/ecam-12-2021-1116
|View full text |Cite
|
Sign up to set email alerts
|

Effect of commitment on the link between organizational culture and international project performance: a comparison between China and Korea

Abstract: PurposeThe purpose of this paper is to verify the mediating role of commitment between market-oriented organizational culture and international market performance, and to discuss the moderator effect of national institutional environment on this mediating role.Design/methodology/approachThe research design follows a mixed methodology, combining qualitative and quantitative data collection and analysis. In the first phase, research hypotheses are proposed based on a literature analysis. In the second phase, sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…Jahanbakhshian (2021) confirmed that organizational commitment contributes to collaboration project performance by promoting trust and knowledge sharing among participating organizations. In a similar vein, Lin et al (2022) argued that organizational commitment strengthens the psychological connection among participating organizations, which helps to achieve high performance of cooperation projects. Previous studies have provided some appealing explanations regarding the role of organizational commitment in promoting interorganizational cooperation.…”
Section: Introductionmentioning
confidence: 99%
“…Jahanbakhshian (2021) confirmed that organizational commitment contributes to collaboration project performance by promoting trust and knowledge sharing among participating organizations. In a similar vein, Lin et al (2022) argued that organizational commitment strengthens the psychological connection among participating organizations, which helps to achieve high performance of cooperation projects. Previous studies have provided some appealing explanations regarding the role of organizational commitment in promoting interorganizational cooperation.…”
Section: Introductionmentioning
confidence: 99%
“…When developing new businesses or products, the research process presents a certain level of subjectivity, establishing the need for evaluation methodologies that allow an analytical approach to projects with these characteristics (Szejka et al, 2017). In this way, related works have explored factors contributing to an improvement of project performance, counting human resource-related factors (e.g., competence (Zhu et al, 2021) or leadership (Lai et al, 2018)), project stakeholder related factors (e.g., conflict (Jia et al, 2021) or issue relationship management (Naji et al, 2022)), and organizational factors (e.g., culture (Lin et al, 2022)). However, it was not recognised related works that evaluate the company issues in order to prioritise the innovation projects according to the corporation's strategic goals.…”
Section: Introductionmentioning
confidence: 99%